Willis's Elements of Quantity Surveying - Lee, Sandra; Trench, William; Willis, Andrew ([S.l.] : Wiley-Blackwell, 2014)
The measurement of building elements is a core subject for quantity surveying students. Responding to the recently published second volume of the New Rules of Measurement (NRM2) by the Royal Institution of Chartered Surveyors, the 12th edition of Willis's Elements of Quantity Surveying explains, from first principles and to NRM2 standards, the measurement process for all the key building elements. This edition begins with an overview of the need for measurement and the differing rules governing measurement at different stages of the design or project cycle. As in previous editions the focus remains the detailed measurement of building elements, but the text has been fully revised in line with the NRM2 rules. A range of new and revised examples illustrating the use of NRM2 rules are a key feature of the book, which concludes with guidance on how to use the data collected during the measurement process to create the tender documents. In the 12th edition the hallmarks of previous editions - clarity and practicality - have been maintained while ensuring the book is fully up to date, providing the student of quantity surveying with a first class introduction to the measurement of building elements.
Keywords: Building -- Quantity surveying; Quantity surveying; Estimates